Characterization and production of novel antioxidative peptides derived from fermented goat milk by L. fermentum. (February 2020) - Panchal, Gauravkumar; Hati, Subrota; Sakure, Amar
Abstract: In the study, goat milk fermented with Lactobacillus fermentum (M4) was analyzed for antioxidant activities (ABTS assay, Hydroxyl free radical scavenging assay & Superoxide free radical assay) found maximum antioxidant activities i.e. ABTS assay (52.27%), hydroxyl free radical scavenging activity (55.73%) and superoxide free radical scavenging activity (43.03%), after 48 h at 37 °C. The growth conditions (inoculation rate and incubation time) were optimized for peptides production through proteolytic activity (OPA method) and found highest (8.44 mg/ml) at 37 °C for 48 h. Then, water soluble extracts from fermented goat milk were analyzed for protein purification using SDS-PAGE and Two-Dimensional (2D) gel electrophoresis and 10–51 kDa protein bands on SDS-PAGE were observed. All spots from 2D were digested by trypsin and identified in RPLC/MS. 3 kDa and 10 kDa permeates were injected into RP-HPLC and then analyzed on RPLC/MS for identification of peptides. The raw masses from LC/MS were identified by using MASCOT analyst software. The aim of study is to purify and characterize the novel antioxidative peptides from fermented goat milk (Indian Surti breed) produced by Lactobacillus fermentum. Highlights: Goat milk has various health benefits. Fermented goat milks contain many physiological bioactive components. Lactic acid bacteria ferment the goat milk for production of bioactive peptides. Antioxidative peptides were identified from fermented goat milk. Novel antioxidant peptides were also found in the fermented goat milk.